Human Short Tandem Repeat (STR) Markers for Paternity Testing in Pig-Tailed Macaques - DYAH PERWITASARI -FARAJALLAH (HAYATI Journal of Biosciences, 2007)
This study investigated the use of human short tandem repeat (STR) or microsatellite loci markers for assessing paternity and genetic structure of pig-tailed macaques (Macaca nemestrina) breeding colony. Four human microsatellite primer pairs located at human map position D1S548, D3S1768, D5S820, and D2S1777, were amplified by polymerase chain reaction (PCR) for pig-tailed macaques. Four loci were found to be clearly and reliably amplified, and three loci exhibited high levels of genetic heterogeneity. These loci were sufficiently informative to differentiate discretely between related and unrelated pairs. Key words: human short tandem repeats (STRs), paternity testing, pig-tailed macaques, Macaca nemestrina